Nurse–physician collaboration in an academic medical centre: The influence of organisational and individual factors. Issue 5 (2nd September 2016) - Bowles, Darci; McIntosh, Georgia; Hemrajani, Reena; Yen, Miao-Shan; Phillips, Allison; Schwartz, Nathan; Tu, Shin-Ping; Dow, Alan W.
ABSTRACT: Ineffective physician–nurse collaboration has been recognised to adversely impact patient and organisational outcomes, and some studies suggest an underlying factor may be that nurses and physicians have different perceptions of interprofessional collaboration (IPC). The objectives of this study were to evaluate for a difference in the perception of IPC between physicians and nurses and to explore potential contributing factors at the individual and organisational levels to any observed difference. Data including measures of perceptions of IPC were collected from a convenience sample of resident physicians ( n  = 47), attending physicians ( n  = 18), and nurses ( n  = 54) providing care for internal medicine patients in a large tertiary care academic medical centre. Regression analysis revealed significantly lower perceptions of IPC scores for nurses in comparison to the scores of both the resident and attending physician groups ( p =  .0001 for both). Although demographic and workload factors also differed by profession, only profession and workload remained significant in regression analysis. Given the known relationships between effective physician–nurse collaboration and superior patient and organisational outcomes, better defining the individual and organisational predictors of IPC scores may support development of more effective interventions targeting improvements in IPC.